1997
DOI: 10.1037/0894-4105.11.3.400
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in category fluency in ischemic vascular dementia.

Abstract: The underlying mechanisms for impaired output on letter (F, A, and S) and category (e.g., animal) word list generation (WLG) tasks in subcortical ischemic vascular dementia (IVD) were investigated. Normal control (NC) and Alzheimer's disease (AD) participants were also studied. IVD and NC participants performed better on category than letter WLG tasks, whereas the opposite was observed among AD participants. IVD participants produced fewer responses than AD participants on letter WLG tasks, but there was no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 51 publications
8
67
0
1
Order By: Relevance
“…Both tests are occasionally referred to as measuring EF, although letter fluency is acknowledged as the most pure form of EF whereas category fluency is often denoted as a test of semantic memory. Interestingly, a dissociation between letter and category fluency tests in VaD and AD patients exists, in that AD patients perform worse on category compared to letter fluency (Carew, Lamar, Cloud, Grossman & Libon, 1997;Henry, Crawford & Phillips, 2004;Monsch et al, 1997) whereas the opposite is found in VaD patients (Carew et al, 1997). Possibly, this dissociation might also be present with respect to the Wechsler subtests, but for now it remains speculative.…”
Section: Discussionmentioning
confidence: 90%
“…Both tests are occasionally referred to as measuring EF, although letter fluency is acknowledged as the most pure form of EF whereas category fluency is often denoted as a test of semantic memory. Interestingly, a dissociation between letter and category fluency tests in VaD and AD patients exists, in that AD patients perform worse on category compared to letter fluency (Carew, Lamar, Cloud, Grossman & Libon, 1997;Henry, Crawford & Phillips, 2004;Monsch et al, 1997) whereas the opposite is found in VaD patients (Carew et al, 1997). Possibly, this dissociation might also be present with respect to the Wechsler subtests, but for now it remains speculative.…”
Section: Discussionmentioning
confidence: 90%
“…Performance on most nonmemory tests was largely intact except for comparatively low output on the "animal" fl uency test. Low output on semantically guided fl uency tests in a group of individuals with anterograde amnesia might suggest the presence of concomitant semantic memory defi cits (Adlam, Bozeat, Arnold, Watson, & Hodges, 2006 ;Carew et al, 1997 ;Dudas, Clague, Thompson, Graham, & Hodges, 2005 ;Murphy, Rich, & Troyer, 2006 ). Howieson at al.…”
Section: Discussionmentioning
confidence: 99%
“…Lexical retrieval/naming was assessed with the 60-item version of the Boston Naming Test (BNT; Kaplan, Goodglass, & Weintraub, 1983 ), and a test of semantic fl uency ("animals"; Carew, Cloud, Lamar, Grossman, & Libon, 1997 ;Monsch, Bondi, Butters, Salmon, Katzman, & Thal, 1992). The dependent variable derived from the BNT was the number of correct responses.…”
Section: Lexical Retrieval/namingmentioning
confidence: 99%
“…In the original, participants arranged animal names mounted on dowels so that closer proximity reflected greater similarity and the examiner measured the distance between labels. We also quantified the degree of semantic feature sharing between our animal exemplars by incorporating a published scoring system (Giovannetti Carew et al, 1997;Moelter et al, 2001). Each animal was scored on six semantic attributes (size, geographic location, diet, zoological class, habitat, and zoological families or groupings) and the number of shared attributes between pairs was computed (see Appendix A).…”
Section: Introductionmentioning
confidence: 99%
“…Each animal was scored on six semantic attributes (size, geographic location, diet, zoological class, habitat, and zoological families or groupings) and the number of shared attributes between pairs was computed (see Appendix A). Reductions in the number of shared attributes between consecutive animal fluency responses has been associated with semantic memory deficits in Alzheimer's disease and left temporal lobe epilepsy (Giovannetti Carew et al, 1997;Giovannetti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%